Análise multifísica e experimentos em sensores ópticos usados na medição de temperatura em rotores de hidrogeradores - LEITE, Reinaldo Corrêa (Universidade Federal do Pará, 2017)
Fiber Bragg gratings (FBGs) offer new possibilities to monitor accurately the rotor temperature. Dozens of sensors can be mounted in series in a single fiber and used to measure the temperature in several points of the rotor winding. Such sensors installed directly on the rotor winding surface are thermally isolated from the cooling air by a silicone layer. Because of the temperature gradient in this structure, the sensor is exposed to thermo-mechanical stresses and therefore can be deformed. Since the FBG probes are sensitive to both temperature and strain, the knowledge of each effect separately is necessary to ensure that the temperature readings are not affected by strain. Experimental results obtained in rotor winding mockup tests with thermistors and FBG sensors show that the temperature readings by the FBG are 4.5°C above the temperature defined by the thermistors which were used as references. Multi-physics simulations were carried out to calculate the strain and temperature in the FBG assembly. The theoretical and experimental results are in a good agreement and show that the temperature gradient across the FBG sensor assembly is sufficient to cause a strain that induces an axial stress in the FBG sensor causing an error in the temperature reading.